2013
DOI: 10.1128/jvi.03433-12
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus Genome Circularization and Efficient Replication Are Facilitated by Binding of PCBP2 and hnRNP A1

Abstract: c Sequences and structures within the terminal genomic regions of plus-strand RNA viruses are targets for the binding of host proteins that modulate functions such as translation, RNA replication, and encapsidation. Using murine norovirus 1 (MNV-1), we describe the presence of long-range RNA-RNA interactions that were stabilized by cellular proteins. The proteins potentially responsible for the stabilization were selected based on their ability to bind the MNV-1 genome and/or having been reported to be involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 88 publications
0
28
0
1
Order By: Relevance
“…For instance, during vRNA replication of RNA viruses, vRI-dsRNAs must be efficiently unwound, thereby releasing nascently synthesized progeny vRNAs from vRNA templates. Moreover, viral genomic and antigenomic RNAs contain multiple cis-acting elements, highly structured RNA regions that usually play pivotal roles in the replication, translation, and encapsidation of vRNAs (11,51). Sometimes, a specific RNA structure required for one vRNA function, like translation or encapsidation, may need disruption and refolding to facilitate another vRNA function, like vRNA replication, and vice versa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, during vRNA replication of RNA viruses, vRI-dsRNAs must be efficiently unwound, thereby releasing nascently synthesized progeny vRNAs from vRNA templates. Moreover, viral genomic and antigenomic RNAs contain multiple cis-acting elements, highly structured RNA regions that usually play pivotal roles in the replication, translation, and encapsidation of vRNAs (11,51). Sometimes, a specific RNA structure required for one vRNA function, like translation or encapsidation, may need disruption and refolding to facilitate another vRNA function, like vRNA replication, and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, a specific RNA structure required for one vRNA function, like translation or encapsidation, may need disruption and refolding to facilitate another vRNA function, like vRNA replication, and vice versa. For example, genomic RNAs or mRNAs of some RNA viruses, including norovirus (13,52,53), flavivirus (12), hantavirus (54), and reovirus (55), can undergo circularization, resulting in the base pairing of vRNA 5= and 3= ends to form panhandle-like structures that may facilitate vRNA translation, encapsidation, or RdRP recruitment to the 3= ends of vRNAs (51,56). However, for initiation of RNA replication, these cyclized vRNA structures need to be disrupted to make the 3= ends of the vRNAs accessible by RdRPs; an example of this type of activity is the chaperoning effect of cypovirus VP5 on cyclized cypoviral mRNAs (25).…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of PCBP2 may damage multiple biological processes through RNAbinding pathways. For instance, PCBP2 could regulate the genome circularization and replication of various RNA viruses, like norovirus (Lopez-Manriquez et al, 2013), severe acute respiratory syndrome coronaviruses (SARS-CoV; Shi et al, 2014), poliovirus (Walter, Parsley, Ehrenfeld, & Semler, 2002), and hepatitis C virus (Li, Masaki, Shimakami, & Lemon, 2014). The upregulation of PCBP2 may contribute to the formation of ribosomal initiation complex, thus enhancing the replication of virus (Asnani, Pestova, & Hellen, 2016).…”
mentioning
confidence: 99%
“…According to the results of Trinkle-Mulcahy et al, the hnRNP proteins, heat shock proteins, ribosomal proteins and multiple cytoskeletal proteins are potential non-specific contaminants using pull-down or immunoprecipitation strategies [31]. However, many studies have revealed that these "nonspecific contaminants" are associated with virus infection through the interactions with viral proteins [52][53][54][55][56][57][58]. Furthermore, previous studies have demonstrated that PCBP2, one of the hnRNP proteins, interacts directly with PRRSV nsp1β [48,49]; inhibition of Hsp90 or Hsp70 attenuates PRRSV replication [50,51].…”
Section: Discussionmentioning
confidence: 99%